EFFICIENCY OF PHYSICAL REHABILITATION OF PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Mykola Maistruk (Lesya Ukrainka Volyn National University, 2017)
The analysis of the effectiveness of physical rehabilitation of patients with chronic obstructive pulmonary disease is carried out. Chronic obstructive pulmonary disease remains one of the most important health problems. In medical, social and economic terms, it is one of the main causes of morbidity and mortality worldwide; people suffer from this disease for years and prematurely die of it or its complications. Chronic obstructive pulmonary disease has a significant negative impact on quality of life, imposing restraints on working capacity, normal physical activity, home occupations, social and family activities, and sleep patterns. The purpose of the research is to study the effectiveness of the proposed method of physical rehabilitation of patients with chronic obstructive pulmonary disease. A comparative analysis of the data of a survey of 162 patients with chronic obstructive pulmonary disease of moderate severity in the process of treatment and physical rehabilitation was conducted. Patients in control groups underwent treatment according to the protocol and rehabilitation according to the generally accepted method, and patients in treatment groups underwent treatment according to the protocol and rehabilitation according to the proposed method. The effectiveness of rehabilitation was assessed by determining changes in the function of external respiration and quality of life parameters during the study. The use of physical rehabilitation in patients with chronic obstructive pulmonary disease has led to an increase in functional capabilities of patients, which was shown by an increase in the mean values of the parameters of external respiration in the study group at the end of the study, which indicate its effectiveness. By virtue of application of the proposed program of physical rehabilitation, it became possible to achieve a significant increase in the overall quality of life and health in patients of the main group by increasing  parameters in problem areas and sub-sectors. Physical rehabilitation should be recommended to patients with chronic obstructive pulmonary disease to help control symptoms, improve quality of life and increase physical activity.